PROGRAM BIMBINGAN PERNIKAHAN BERBASIS PEMULIHAN TRAUMA RELASIONAL BAGI PEREMPUAN PASCA PERCERAIAN: PENGEMBANGAN MATERI ACUAN KONSELING - Budiarda Widya Laksana Budiarda (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2026)
The high divorce rate in Indonesia, particularly in Ngawi Regency where the majority of cases are filed by wives, presents serious psychological challenges for post-divorce women planning to remarry. This study aims to develop comprehensive, evidence-based marriage guidance reference materials for divorced women, focusing on relational trauma recovery as the foundation for remarriage readiness. This study employs a library research approach with a systematic analysis of Scopus-indexed empirical literature from 2015–2025. Integrated theories include Adult Attachment Theory (Bowlby), Trauma Recovery Theory (Herman), Cognitive-Behavioral Therapy, and the Gottman Method Couples Therapy. The findings indicate that marriage readiness in post-divorce women requires multilayered interventions encompassing: (1) relational trauma recovery and cognitive schema restructuring regarding marriage; (2) strengthening emotion regulation and secure attachment patterns; (3) developing assertive communication and conflict resolution skills; and (4) marriage readiness assessment based on emotional, cognitive, social, and interpersonal dimensions. This article produces a modular design of a five-session thematic marriage guidance program adaptable by counselors at Religious Affairs Offices (KUA) and Islamic counseling institutions. The contribution of this research is expected to address the gap in pre-marital guidance services that have not specifically targeted post-divorce women. Keywords: marriage guidance; divorce; relational trauma; marriage readiness; Islamic counseling